Peran Asia Muslim Charity Foundation Dalam Pengembangan Manajemen Pendikan Islam di Ma’had Al-Birr Universitas Muhammadiyah Makassar - Bakri, Muhammad Ali (Badan Litbang dan Diklat Kementerian Agama RI, 2023)
Asia Muslim Charity Foundation (AMCF) as an Islamic philanthropic institution has been a very important role in the sustainability and improvement of the quality of Islamic education in Indonesia. This research aims to formulate and describe the role of AMCF as an Islamic philanthropic in developing education at the Ma'had Al-Birr Muhammadiyah University of Makassar. This research used a descriptive-qualitative approach. Data collection techniques used open interviews, direct observation, and documentation studies. The results of the research show that first, the successful implementation of education at Ma'had Al-Birr is due to the high commitment of Ma'had leaders and Unismuh Makassar in carrying out the vision, mission, and goals of Ma'had education. Second, the form of educational management development implemented at Ma'had Al-Birr is the development of physical infrastructure, human resource development, and the transformation of Ma'had into the Undergraduate (S1) program. The transformation of Ma'had to the bachelor program includes teacher management, leadership management, curriculum management, facilities and infrastructure management, student management, and financial management which are integrated with the academic system of the University of Muhammadiyah Makassar.